Dr. Strange, Are We Experiencing the Same? Perceptions of the Metaverse Among Gamers, by Gender - Cruz, M.; Oliveira, A. (Proceedings of the 2024 3rd Eurasian Conference on Frontiers of Computer Science and Information Technology (FCSIT 2024). Learning and Analytics in Intelligent Systems, 2025)
On the wave of a great digital revolution, virtual reality enables immer- sive experience in cyberspace via various devices, gliding virtual worlds in a dynamic multiverse. To what extent can a ﬁlm focused on the multiverse be linked to the perceptions of the Metaverse among Portuguese adults? And, more: Are there signiﬁcant differences between men’s and Women’s perceptions? In this context, we aim to verify the representations of the Metaverse of each gender and verify the importance of a ﬁlm (related to the Metaverse and the multiverse) on these representations. Embracing technological advancements is crucial for soci- etal progress, with ﬁlms playing a signiﬁcant role in conveying complex concepts and fostering acceptance through immersive storytelling and virtual reality. Fic- tional narratives, especially those enhanced by technology, can shape attitudes and beliefs, demonstrating the transformative potential of virtual reality and ﬁction. This study emphasises the relevance of gamers in understanding and engaging with the concepts of Metaverse and multiverse.